Stratigraphic revision of the early Miocene Kiahera Formation from Rusinga Island, Lake Victoria, Kenya. (April 2023) - Michel, Lauren A.; Peppe, Daniel J.; Cheng, Kimberly D.; Summers, Hunter; Leimer, H. Wayne; Lehmann, Thomas; Muteti, Samuel; McNulty, Kieran P.
Abstract: Decades of research in Early Miocene deposits on Rusinga Island, Lake Victoria, Kenya, have made its fossil record pivotal for interpreting floral and faunal evolution in eastern Africa during the early Neogene. Paleontological research has largely focused on Rusinga Island's fossil-rich Hiwegi Formation, and because that work has largely motivated geological research a similar bias can also be found in stratigraphic studies of the island's deposits. Hence, the resolution of paleoclimate, paleohabitat, and floral and faunal community reconstructions from other formations is limited, and discrepancies in stratigraphic placement and correlations among outcrops limit our ability to fully assess the interplay of climate and evolution. New lithostratigraphic and sedimentologic analyses of the Kiahera Formation on Rusinga Island clarify these discrepancies. Our work demonstrates that the Kiahera Formation comprises ten facies and can be divided into three discrete clastic units (from bottom to top): Nyamita Spring Member, Ukowe Member, and Rondo Member. The lithofacies in the formation are composed of conglomerates, sandstones, airfall tuffaceous units, and paleosols. Conglomerates, sandstones, and paleosols are found primarily within fluvially-dominated sediments in the Nyamita Spring and Rondo Members, interpreted to represent little to no volcanic input. Tuffaceous units occur within the middle Ukowe Member and record a series of eruptions of the neighboring Kisingiri Volcano. Importantly, reassessment of the type section of the Wayando Formation, which previous researchers identified as the oldest formation on Rusinga Island, demonstrates that it is stratigraphically and lithologically equivalent with the upper member of the Kiahera Formation. Other deposits historically attributed to the Wayando Formation can likewise be correlated with sections of the Kiahera Formation. Hence, the Kiahera Formation represents the oldest sediments on Rusinga. Finally, our revised descriptions and analysis enabled us to identify the basal member of the Kiahera Formation in outcrops on neighboring Mfangano Island, but stratigraphically well above where previous researchers had positioned them. This provides a new basis for interpreting the relationship between Mfangano Island's important fossil assemblages and the better-known assemblages from Rusinga Island. In total, clarification and consolidation of Rusinga Island's Kiahera Formation significantly impact paleontological and paleoecological characterizations of this unit and of the entire Early Miocene geological sequence on the island, further informing interpretations of how Rusinga's fossil sites formed with respect to the evolving Kisingiri Volcano. Highlights: New stratigraphic study of fossil-bearing deposits from Early Rusinga Island is presented. Lithostratigraphy suggests the Kiahera Fm is composed of 3 members, which are formally named. Wayando Fm is comprised of the same facies as the upper Kiahera, Fm., suggesting misidentification. These revisions facilitate greater palaeoecological and paleontological characterization of the Kiahera. This study elucidates the relationship of the Kiahera Fm. with other strata on Rusinga and neighboring islands.